Association between chronic osteomyelitis and deep-vein thrombosis - Lin, Te-Yu; Chen, Yu-Guang; Huang, Wen-Yen; Lin, Cheng-Li; Peng, Chiao-Ling; Sung, Fung-Chang; Kao, Chia-Hung (Thrombosis and Haemostasis, 2014)
Studies on the association between chronic osteomyelitis and deep vein thrombosis (DVT) and pulmonary thromboembolism (PE) are scarce. The aim of this study was to analyse a nationwide population-based database for association between DVT or PE after a diagnosis of chronic osteomyelitis. This nationwide population-based cohort study was based on data obtained from the Taiwan National Health Insurance Database from 1998 to 2008, with a follow-up period extending to the end of 2010. We identified patients with chronic osteomyelitis using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes. The patients with chronic osteomyelitis and comparison controls were selected by 1:1 matching on a propensity score. The propensity score was calculated by a logistic regression to estimate the probability of the treatment assignment given the baseline variables including age, sex, and Charlson comorbidity index score. We analysed the risks of DVT and PE by using Cox proportional hazards regression models, including sex, age, and comorbidities. In total, 24,335 chronic osteomyelitis patients and 24,335 controls were enrolled in the study. The risk of developing DVT was 2.49-fold in patients with chronic osteomyelitis compared with the comparison cohort, after adjusting for age, sex, and comorbidities. The multiplicative increased risks of DVT were also significant in patients with chronic osteomyelitis with any comorbidity. In conclusion, physicians should consider chronic osteomyelitis in their evaluation of risk factors for DVT.
Keywords: Chronic osteomyelitis; deep vein thrombosis; pulmonary embolism